N 6 -methyladenosine regulates glycolysis of cancer cells through PDK4 - Li, Zihan; Peng, Yanxi; Li, Jiexin; Chen, Zhuojia; Chen, Feng; Tu, Jian; Lin, Shuibin; Wang, Hongsheng (Nature communications, 2020)
Studies on biological functions of N -methyladenosine (m A) modification in mRNA have sprung up in recent years. We find m A can positively regulate the glycolysis of cancer cells. Specifically, m A-sequencing and functional studies confirm that pyruvate dehydrogenase kinase 4 (PDK4) is involved in m A regulated glycolysis and ATP generation. The m A modified 5'UTR of PDK4 positively regulates its translation elongation and mRNA stability via binding with YTHDF1/eEF-2 complex and IGF2BP3, respectively. Targeted specific demethylation of PDK4 m A by dm ACRISPR system can significantly decrease the expression of PDK4 and glycolysis of cancer cells. Further, TATA-binding protein (TBP) can transcriptionally increase the expression of Mettl3 in cervical cancer cells via binding to its promoter. In vivo and clinical data confirm the positive roles of m A/PDK4 in tumor growth and progression of cervical and liver cancer. Our study reveals that m A regulates glycolysis of cancer cells through PDK4.